ISLAMISASI ADAT MINANGKABAU MELALUI PEMBERDAYAAN LEMBAGA SURAU: SEBUAH STUDI ANALISIS SEJARAH PADA ABAD KE-17 - Muhammad Sayyid Mufid (Pascasarjana Universitas Al-Qolam Malang, 2026)
Indonesia is known as the country with the second-largest Muslim majority in the world. Historically, Islam entered Indonesia in the 13th century through trade routes in the Strait of Malacca. The extensive spread certainly creates a diversity of Indonesian Islamic culture, where each region has its distinctive style. The Minangkabau people are a community that adheres to Islamic teachings, where Islam has merged with customs and vice versa. One of the known methods of spreading Islam in Minangkabau is through Surau, which is a traditional Islamic educational institution. The article focuses on the spread of Islam in Minangkabau through Surau, considering the socio-cultural context of that century. It also examines the character of Islam introduced by the central figure, Sheikh Burhanuddin Ulakan, who brought the Sufi teachings of the Syatariyah order. The related questions are how Islam spread in Minangkabau, what conditions of the Minangkabau customary culture allowed for the acceptance of Islamic teachings, and why Minangkabau customary culture not only accepted but also integrated these teachings, transforming old customs into practices based on Sharia. The article employs qualitative analysis with a historical approach, referencing history books, documents, and related articles. The central argument presented is that the Islam applied to Minangkabau customs is not an Islam that erases culture but can synergize with it.